2019
DOI: 10.3390/molecules24193626
|View full text |Cite
|
Sign up to set email alerts
|

Red Wine Consumption and Cardiovascular Health

Abstract: Wine is a popular alcoholic beverage that has been consumed for hundreds of years. Benefits from moderate alcohol consumption have been widely supported by the scientific literature and, in this line, red wine intake has been related to a lesser risk for coronary heart disease (CHD). Experimental studies and meta-analyses have mainly attributed this outcome to the presence in red wine of a great variety of polyphenolic compounds such as resveratrol, catechin, epicatechin, quercetin, and anthocyanin. Resveratro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
144
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(148 citation statements)
references
References 131 publications
3
144
1
Order By: Relevance
“…The polyphenolic and flavonoid content of M. oleifera seed extracts used in the present study is in the range reported for defatted seed extracts in other studies (Singh et al 2013;Nascimiento et al 2017;de la Mora-López et al 2018). This reflects the antioxidant capacity of the extract since it is widely known that both phenolic and flavonoid compounds possess high antioxidant activity (Covas et al 2010;Castaldo et al 2019;Olszowy 2019). Although other studies have reported a protective effect of the addition of antioxidants, such as hypotaurine, on acrosome integrity and mitochondrial activity (Bucak et al 2013), this investigation did not find any significant effect of the M. oleifera extract on either the acrosomal status or mitochondrial activity in cryopreserved ram sperm.…”
Section: Discussioncontrasting
confidence: 58%
“…The polyphenolic and flavonoid content of M. oleifera seed extracts used in the present study is in the range reported for defatted seed extracts in other studies (Singh et al 2013;Nascimiento et al 2017;de la Mora-López et al 2018). This reflects the antioxidant capacity of the extract since it is widely known that both phenolic and flavonoid compounds possess high antioxidant activity (Covas et al 2010;Castaldo et al 2019;Olszowy 2019). Although other studies have reported a protective effect of the addition of antioxidants, such as hypotaurine, on acrosome integrity and mitochondrial activity (Bucak et al 2013), this investigation did not find any significant effect of the M. oleifera extract on either the acrosomal status or mitochondrial activity in cryopreserved ram sperm.…”
Section: Discussioncontrasting
confidence: 58%
“…Taking as example, resveratrol, one of the most studied natural compounds lately, we saw that its low bioavailability and fast metabolism make difficult to estimate the correct dose for the targeted effect [181]. Studies have been shown that the cardiac protective effects of resveratrol observed at doses between 2.5 and 5 mg/kg/day were reversed when the doses were increased to doses of 25-50 mg/kg/day [182]. Another problem in translating the results from animals to humans is associated with safety and efficacy in humans that definitely needs the development of clinical safety trials and evaluation of potentially drug interactions that can have negative effects on the individual.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…The non-flavonoid phenolic constituents in wine are divided into hydroxybenzoic acids and hydroxycinnamic acids, stilbenes and other miscellaneous compounds [ 43 ]. These phenolic compounds can reach levels that range from 60 to 566 mg/L [ 44 ].…”
Section: Non-flavonoidsmentioning
confidence: 99%